2013
DOI: 10.4314/jasem.v17i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Review on Chemical treatment of Industrial Waste Water

Abstract: Industrialization played an important role for scio-economy of the country. Generally, a lot of water is used and lot of wastewater generated from industries due their processes and washing purpose. A large number of chemicals are used for the production of potable water and in the treatment of wastewater effluents. In potable water treatment chemicals such as inorganic salts and polymeric organic coagulants are used for primary coagulation, as coagulant aids and for sludge dewatering; lime and soda ash allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 72 publications
2
106
0
7
Order By: Relevance
“…Moreover, large tonnage use of inorganic compounds produces higher volumes of sludge. Among polymeric flocculants, the synthetic polymers can be tailor made by controlling molecular weight, molecular weight distribution, the structure of polymers and the nature and percentage of ionic groups 5,6 . During the last 30 years, the production of polymeric flocculants has rapidly increased.…”
Section: Abstract: Poly(acrylamide-co-acrylic Acid) Synthesis Absormentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, large tonnage use of inorganic compounds produces higher volumes of sludge. Among polymeric flocculants, the synthetic polymers can be tailor made by controlling molecular weight, molecular weight distribution, the structure of polymers and the nature and percentage of ionic groups 5,6 . During the last 30 years, the production of polymeric flocculants has rapidly increased.…”
Section: Abstract: Poly(acrylamide-co-acrylic Acid) Synthesis Absormentioning
confidence: 99%
“…Flocculation refers to the successful collision that occurs when destabilized particles are driven toward each other by the hydraulic shear force in the rapid mix and flocculation basin. It agglomerates of a few colloids then quickly bridge together to form microflocs which is turned into visible floc masses 5 . Coagulation happens by the addition in the water to be treated of inorganic salts, based on aluminium or iron (aluminium sulfate -alum, ferric sulfate, ferric chloride, ferrous sulfate, and sodium aluminate) while flocculation happens by the addition of organic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The required ferrous sulphate dosage is considerably high, at more than 1,000 ppm although in earlier study conducted shown the optimum dosage of ferrous sulphate for POME treatment was between 200-300 ppm [13]. The higher dosage was due to higher pH range during the aerobic treatment, whereby the pH was above 8.0 as against the optimum operating pH for metal based polymer coagulation process at pH 4 to 5 [15]. This reduction was due to the higher concentration of OH -ion that will compete with organic molecules for adsorption sites.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally referred to as alum. Occasionally certain synthetic organic chemicals, addressed polymers are added together along with the alum to act as coagulant aids [4]. The alum sludge is commonly mechanically dewatered and is currently treated as a waste which cannot be processed through conventional sewage sludge disposal methods and in many cases goes to landfill.…”
Section: A Alum Sludgementioning
confidence: 99%